Cultures of stone : an interdisciplinary approach to the materiality of stone - Cooney, Gabriel; Gilhooly, Bernard; Kelly, Niamh; Mallía-Guest, Sol (Sidestone Press, 2020)
This volume establishes a rich cross-disciplinary dialogue about the significance of stone in society across time and space. The material properties of stone have ensured its continuing importance; however, it is its materiality which has mediated the relations between the individual, society and stone. 0Bound up with the physical properties of stone are ideas on identity, value, and understanding. Stone can act as a medium through which these concepts are expressed and is tied to ideas such as monumentality and remembrance; its enduring character creating a link through generations to both people and place. 0This volume brings together a collection of seventeen papers which draw on a range of diverse disciplines and approaches; including archaeology, anthropology, classics, design and engineering, fine arts, geography, history, linguistics, philosophy, psychology and sciences.